2013
DOI: 10.1186/1471-2164-14-554
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, evolutionary and expression analysis of the aspartic protease gene superfamily in grape

Abstract: BackgroundAspartic proteases (APs) are a large family of proteolytic enzymes found in almost all organisms. In plants, they are involved in many biological processes, such as senescence, stress responses, programmed cell death, and reproduction. Prior to the present study, no grape AP gene(s) had been reported, and their research on woody species was very limited.ResultsIn this study, a total of 50 AP genes (VvAP) were identified in the grape genome, among which 30 contained the complete ASP domain. Synteny an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 89 publications
8
56
0
1
Order By: Relevance
“…This result suggests that both HK1 proteins can also have a specific partnership with HPts. As described in Arabidopsis , duplicates tend to have different interaction partners [43,44] and we confirmed this hypothesis for HK1 duplicates. Knowing that HPt7 is mainly expressed in roots [30], this different behavior of both HK1s towards this HPt could lead to a different involvement of these two paralogs in the drought signaling pathway in poplar roots.…”
Section: Discussionsupporting
confidence: 89%
“…This result suggests that both HK1 proteins can also have a specific partnership with HPts. As described in Arabidopsis , duplicates tend to have different interaction partners [43,44] and we confirmed this hypothesis for HK1 duplicates. Knowing that HPt7 is mainly expressed in roots [30], this different behavior of both HK1s towards this HPt could lead to a different involvement of these two paralogs in the drought signaling pathway in poplar roots.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, a total of 27 LEA family members have been identified in tomato and divided into 7 groups based on sequence similarities to the Arabidopsis LEAs (Hundertmark and Hincha 2008). Comparative genomic analysis is an effective method for studying gene structures (Guo et al 2013). In this study, we assessed the conserved motifs of the predicted LEA proteins in Arabidopsis and tomato by the MEME program.…”
Section: Discussionmentioning
confidence: 99%
“…Aspartic proteases (APs) are a large family of proteolytic enzymes found in nearly all organisms. In plants, they are involved in many biological processes, including senescence, stress responses, programmed cell death, and reproduction (Chen et al, 2009;Guo et al, 2013). According to Contour-Ansel et al (2010), water stress in bean led to the gene expression regulation of an AP gene (PvAP1) both at the transcriptional and post-transcriptional levels, which is paramount in the conservation of cellular homeostasis and recovery.…”
Section: Discussionmentioning
confidence: 99%